2006
DOI: 10.1212/01.wnl.0000231513.23919.a1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pramipexole in restless legs syndrome

Abstract: As rated by patients and by clinicians, pramipexole was efficacious and safe in reducing the symptoms of restless legs syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
103
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(116 citation statements)
references
References 34 publications
8
103
2
3
Order By: Relevance
“…The degree of improvement with bupropion was similar to the improvement seen with dopamine agonists currently approved for the treatment of moderate to severe RLS. 10,11 In our study, bupropion did not exacerbate the symptoms of RLS. This contrasts with other antidepressants, which have been shown to exacerbate symptoms.…”
Section: Discussionsupporting
confidence: 47%
“…The degree of improvement with bupropion was similar to the improvement seen with dopamine agonists currently approved for the treatment of moderate to severe RLS. 10,11 In our study, bupropion did not exacerbate the symptoms of RLS. This contrasts with other antidepressants, which have been shown to exacerbate symptoms.…”
Section: Discussionsupporting
confidence: 47%
“…20 The reductions in IRLS total score observed in the present study are also comparable with those reported for dopamine agonists that are currently approved for treatment of RLS. [31][32][33][34][35] A significant mean reduction in IRLS total score from baseline was also reported with GEn 600 mg (-13.8) compared with placebo (-9.8), and a greater proportion of GEn 600 mg-treated subjects were rated by investigators as CGI-I responders (72.8% compared with 44.8%, respectively). These results contrast with findings from a 2-week study of GEn 600 mg reported by Walters et al that demonstrated a nonsignificant mean reduction from baseline in IRLS total score at Week 2 LOCF (-9.1) compared with placebo (-8.9), and no significant difference in the proportion of CGI-I responders (GEn 600 mg, 58.6%; pla- jects in the present study reported significant sleep disturbance at baseline on the MOS Sleep Scale domains compared with a healthy cohort sample of the US population.…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что ДС развивается при приеме пра-мипексола здоровыми и пациентами с синдромом беспокойных ног [17,18], при этом она наиболее выражена в период с 15:30 до 17:30 [19,20]. В иссле-дованиях ротиготина и ропинирола ДС в основных группах возникала в 2 раза чаще в сравнении с груп-пой плацебо, но без развития императивных засы-паний [21][22][23].…”
Section: дс -побочный эффект дофаминергической терапии?unclassified